NCOG-06. CASE REPORT: EXTENDED REMISSION OF HER2-POSITIVE BREAST CARCINOMA WITH BRAIN METASTASES AND LEPTOMENINGEAL DISEASE FOLLOWING INTRATHECAL AND SYSTEMIC TRASTUZUMAB. (14th November 2022) - Gregory, Timothy; Loghin, Monica
Abstract: Leptomeningeal disease (LMD) in breast cancer carries a poor prognosis with median overall survival (OS) of 3-4 months. Recent series have indicated prolongation of OS up to 10-13 months in HER2-positive breast LMD treated with intrathecal (IT) trastuzumab. Here we present an unprecedented long-term survival with clinical, radiographic, and molecular response for more than 10 years on IT trastuzumab. A 52-year-old woman presented in 12/2011 with newly diagnosed LMD with previously treated brain and systemic metastases. Her initial diagnosis of HER2-positive left intraductal carcinoma in 5/2005 was treated with bilateral mastectomy, adjuvant chemotherapy with doxorubicin and cyclophosphamide followed by paclitaxel and trastuzumab, as well as local RT. She was disease free until 10/2009 when she presented with headache due to two brain metastases involving the vermis and right occipital lobe. She underwent resection and SRS, followed by chemotherapy with capecitabine and lapatinib. In 12/2010 she received further RT to the posterior fossa for recurrent disease and later required gamma knife to a left occipital metastasis. In 8/2011 she developed back pain and cauda equina syndrome. MRI spine revealed LMD from T11- L2. CSF studies showed > 500 protein, 17 WBCs and malignant cells consistent with her breast primary. Both cerebellar metastasis and cells in the spinal fluid showed over-expression and amplification of HER2neu. She completed RT to the lower spine, and in 1/2012 began IT trastuzumab with continuation of capecitabine and lapatinib. There was progressive LMD in 2/2012 prompting escalation of IT trastuzumab dosing and addition of IT topotecan with systemic trastuzumab. In 10/2019, CSF showed rare malignant cells and IT topotecan was switched to cytarabine while continuing IT trastuzumab, now with durable remission ever since. The low LMD burden and aggressive therapeutic approach, including IT trastuzumab, combined with radiation and systemic therapy may explain the exceptional survival.